2020
DOI: 10.46234/ccdcw2020.037
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Leisure-Time Physical Activity Among Chinese Adults — China, 2000–2015

Abstract: What is already known about this topic? The monitoring report on nutrition and health status of Chinese residents from 2010 to 2013 reported that the participation rate of leisure-time physical activity (LTPA) was 13.8% among those 6 years and older. What is added by this report? Among 18 years old and older, the age-standardized LTPA prevalence increased from 7.13% in 2000 to 11.79% in 2011 before dropping to 7.33% in 2015. What are the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…One MET represents the resting energy expenditure during quiet sitting. In our study, one minute of VPA is equivalent to 7.5 METs, and 4.5 METs for MPA [9]. The volume of MVPA was classified by the minimum and maximum of the recommendation in the guideline (no activity, 45-675 METs, 676-2250 METs, >2250 METs).…”
Section: Assessment Of Physical Activitymentioning
confidence: 87%
See 1 more Smart Citation
“…One MET represents the resting energy expenditure during quiet sitting. In our study, one minute of VPA is equivalent to 7.5 METs, and 4.5 METs for MPA [9]. The volume of MVPA was classified by the minimum and maximum of the recommendation in the guideline (no activity, 45-675 METs, 676-2250 METs, >2250 METs).…”
Section: Assessment Of Physical Activitymentioning
confidence: 87%
“…Although the prevalence of leisure-time physical activity (LTPA) and the proportion of residents to reach the vigorous-intensity level had been increasing among adults aged 18 years and above, they were still at a low level according to China Health and Nutrition Survey. [9] Limited by comorbidity and aging factors, a greater number of middle and older aged adults failed to achieve the goal of keeping physically active.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other domains of physical activity, such as for work, for housework, and for transportation, LTPA was found to be better for preventing cardiovascular disease and protecting cognition (4). In China, 83.8% of adults reported no LTPA, and only 11.9% of adults aged 18 years old and above engaged in the regular LTPA in 2010 (5). It was reported that the age-standardized LTPA prevalence increased from 7.13% in 2000 to 11.79% in 2011 (6).…”
Section: What Are the Implications For Public Health Practice?mentioning
confidence: 99%
“…In contrast, physical inactivity is responsible for almost one sixth of the direct (medical) and indirect (nonmedical) yearly costs for the management of chronic diseases [9]. Despite its health and economic bene ts, participation in PA among Chinese adults remains low [10].…”
Section: Introductionmentioning
confidence: 99%